Perception of FA by Non-native Listeners in a Study Abroad Context - Avello, Pilar; Mora, Joan Carles; Pérez-Vidal, Carmen (Research in Language, 2012)
The present study aims at exploring the under-investigated interface between SA and L2 phonological development by assessing the impact of a 3-month SA programme on the pronunciation of a group of 23 Catalan/Spanish learners of English (NNSs) by means of phonetic measures and perceived FA measures. 6 native speakers (NS) in an exchange programme in Spain provided baseline data for comparison purposes. The participants were recorded performing a reading aloud task before (pre-test) and immediately after (post-test) the SA. Another group of 37 proficient non-native listeners, also bilingual in Catalan/Spanish and trained in English phonetics, assessed the NNS' speech samples for degree of FA. Phonetic measures consisted of pronunciation accuracy scores computed by counting pronunciation errors (phonemic deletions, insertions and substitutions, and stress misplacement). Measures of perceived FA were obtained with two experiments. In experiment 1, the listeners heard a random presentation of the sentences produced by the NSs and by the NNSs at pre-test and post-test and rated them on a 7-point Likert scale for degree of FA (1 = “native” , 7 = “heavy foreign accent”). In experiment 2, they heard paired pre-test/post-test sentences (i.e. produced by the same NNS at pre-test and post-test) and indicated which of the two sounded more native-like. Then, they stated their judgment confidence level on a 7-point scale (1 = “unsure”, 7 = “sure”). Results indicated a slight, non-significant improvement in perceived FA after SA. However, a significant decrease was found in pronunciation accuracy scores after SA. Measures of pronunciation accuracy and FA ratings were also found to be strongly correlated. These findings are discussed in light of the often reported mixed results as regards pronunciation improvement during short-term immersion.